The Essence of Mahabah from the Perspective of Sheikh Abdul Qadir Jailani: A Study of The Tafsir of Al-Jilani - Najiburrohman, Najiburrohman; Mariatin, Siti (Universitas Muhammadiyah Surakarta, 2023)
Islam is a religion that guides people in life to always be guided. Islam also recognizes one of the natures of the human heart in the form of love. Discussions about love (mahabah) have been studied a lot, but not all of them focus on mahabbatullah. The themes discussed are an explanation of love towards fellow beings, such as spouse, family, property, and place of residence. Believers nowadays have a greater level of love for others than Allah and prefer worldly happiness to attain the love of Allah. In Tafsir Al-Jailani, written by Sheikh Abdul Qadir Jailani, the essence of love belongs only to and for Allah swt. This tafsir, it complements the explanation of mahabah written by other Sheikh Abdul Qadir, although the discussion in Tafsir Al-Jailani is less long and extensive. The characteristic of Tafsir Al-Jilani has a Sufi pattern and uses the ijmali method. In the sense of an interpretation, it cannot be separated from its scientific background, as well as Sheikh Abdul Qadir al-Jailani, in his interpretation, must have been influenced by Sufi thought. The method used in this research is descriptive analysis by systematically, factually, and accurately describing the phenomenon under study. The results of this research show that true love is love that flows to the owner of a majesty, namely Allah swt. Love for anything will be false if it is not aimed at Him. When the sense of compassion flows in every human being, it will give rise to behaviors that are inclined towards obedience in everyday life.